Alpha IVBO - Construction of a scale to measure the illusion of virtual body ownership - Roth, Daniel; Lugrin, Jean Luc; Latoschik, Marc Erich; Huber, Stephan (Conference on Human Factors in Computing Systems - Proceedings, 2017)
In this paper, we present a scale construction and its initial test as a step towards a standardized measure of the illusion of virtual body ownership (IVBO) in virtual simulations. The IVBO describes the effect of users partly or fully perceiving a virtual body as their own. We analyzed components for a scale we call "Alpha IVBO" by using data from a fake mirror scenario study. Users saw their movements mapped in real-time to a virtual avatar rendered on 3D display placed in front of them. The principal component analysis of our sample data resulted in three factors: "acceptance", "control" and "change".
CRIS-Team Scopus Importer:2021-03-29
Keywords: Avatars; Embodiment; Virtual body ownership